Structural and Magnetic Characterization of the Tridimensional Network [Fe(Hco2)3]N·Nhco2h - Venegas-Yazigi, D; Venegas-Yazigi, D (2013)
In this work we report the structural and magnetic characterization of a new three-dimensional porous metal-organic framework (MOF) based on iron(iii) and the formate anion, [Fe(HCO2)3]n· nHCO2H (1), which was obtained by solvothermal synthesis. The tridimensional structure crystallizes in the trigonal space group R3c and is formed by highly regular octahedral Fe(OHCO)6 units. These units contain six equal Fe-O distances, with angles slightly different from 90°or 180°. The packing of 1 corresponds to a 3D covalent network defined by face sharing between the parallelepipeds, which are formed by the interactions of Fe(OHCO)6 units through formate ligands, thus generating a 4 1263 topology. This topology contains channels in the three spatial directions, in which it is possible to find guest molecules of formic acid. The thermogravimetric analysis shows that 1 remains stable till 180 °C; after this temperature the decomposition of 1 begins. From a magnetic point of view, the reported MOF presents an antiferromagnetic behaviour in the 296 to 20 K range. The fit of the experimental data between room temperature and 50 K, using the high temperature series model (HTS model), permits us to estimate a J value of -1.01 cm-1, which is in agreement with the reported values for analogous systems based on transition metal ions and formate ligands. Below this temperature, a weak ferromagnetism as a product of spin canting was observed due to the anti-anti coordination mode of the bridging ligand, which satisfies the requirement for Dzyaloshinsky-Moriya antisymmetric interactions between the FeIII ions. The isothermal magnetization obtained at 2 K shows that the magnetization increases linearly with the applied magnetic field, reaching a value of 0.49N? at the highest applied field of 50 kOe, indicating the antiferromagnetic character of the ground state. DFT calculations using a dinuclear fragment confirm the magnitude and nature of the magnetic phenomena of this extended system at high temperatures. © 2013 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.